Explaining Policy Reform Implementation in Guinea: The Role of both Internal and External Factors - Jennifer Clapp (Journal of International Development, 1994)
This paper examines the factors which affected the implementation of structural adjustment  reforms in Guinea, a country which to date has received  little attention, but which has experienced many of the classic problems of policy reform implementation. It is found that while recent attention given to domestic factors such as governance and institutional capacity in explaining the poor adjustment implementation record in Africa are justified, external factors such as donor behaviour and world market conditions played an equally important role. These domestic and external factors in Guinea affected not only the adoption and actual implementation of specific reform measures, but also the state’s overall commitment to maintaining the adjustment programme once it was in place.